Relationship between the gold price and the Australian dollar - US dollar exchange rate - Haque, M.; Topal, Erkan; Lilford, E. (Springer, 2015)
The United States (US) dollar-based gold price and the exchange rate between the Australian dollar and the US dollar (AUD/USD) have a combined and significant impact on both the trend of the Australian minerals industry and the overall Australian economy. The trend in this case refers to the economic sustainability and growth of the minerals industry as well as the physical extraction and production rates of the collective industry. To estimate gold mining project values, it is necessary to determine the correlation between the gold price, stated in US dollars per ounce (US$/oz), and the relevant exchange rate, being the Australian dollar against the US dollar (AUD/USD). In this empirical study, the aim is to investigate the long - run relationship between the US quoted gold price and the relevant periodic exchange rates (AUD/USD), and to determine the correlation coefficient between them using weekly average data over the period 1996 to 2014. In addition, the continuously compounded percentage return series for gold prices and AUD/USD exchange rates has been calculated, the results of which have exposed an interesting finding in that a bi-directional causality exists between the continuously compounded percentage return of periodic gold prices and the returns of the commensurate AUD/USD exchange rates. Especially for approximating mining project values, mine managers and other decision makers need to be cautious about different uncertainties including financial and economic uncertainties, and the inter correlation and long term relationships among economic variables. AAugmented Dickey-Fuller (ADF) and modified Dickey-Fuller methods of analysis have been performed using generalised least squares (DF-GLS) tests to examine whether the time series data are stationary. Arising from this it has been observed that all of the tests have confirmed both the gold price and the AUD/USD exchange rate data series are I (1) stationary at a 1 % significance level. In addition, Johansen cointegration tests for examining the long – run relationship have been performed, and it was determined that there is a long term relationship between the gold price and the exchange rate (AUD/USD). Vector auto regression (VAR) tests revealed that there is bi-directional causality between the gold price and the AUD/USD exchange rate, and it is also supported by the structural vector auto regression (SVAR) impulse – response functions (IRFs) analysis. Furthermore, the study revealed that a strong positive correlation between the gold price and the AUD/USD exchange rate exists, and it also exposed that a one percent increase in the nominal gold price leads to an appreciation of the AUD/USD nominal exchange rate by approximately 0.5 %.